Implementation of a novel living-donor kidney transplant preoperative checklist within the electronic medical record: a pilot study. Issue 1 (December 2015) - Gill, Bradley; Arora, Hans; Kerr, Hannah; Flechner, Stuart; Ellis, Courtney; Goldfarb, David
Abstract Background Checklist utilization in surgery has contributed to improved patient safety and reduced numbers of preventable complications. A living-donor kidney transplant (LDKT) preoperative checklist embedded within electronic medical record (EMR) was developed to enhance patient safety and prevent "never" events including: unexpected donor-recipient blood (ABO) incompatibility, positive (XM) cross match, infectious disease transmission, or procurement of an anatomically inappropriate allograft. Review of the initial 2 years of checklist utilization was performed. Findings This safety instrument operates by facilitating critical review and referencing of source documentation to confirm ABO, XM, infectious risk, and organ anatomy compatibility. It was met with high compliance rates and no "never events" have occurred following its inception. The checklist is readily available in the EMR and is accessible by all members of the LDKT recipient healthcare team. Conclusions Checklist utilization was associated with zero LDKT "never event" occurrences. Surgeons felt the checklist was easy to use.